A comprehensive review on biochar for electrochemical energy storage applications: an emerging sustainable technology - Prabakar, Ponnusamy; Mustafa Mert, Koc; Muruganandam, Logananthan; Sivagami, Krishnasamy (Frontiers in Energy Research, 2024)
Energy is an essential factor in many activities. The need to generate adequate energy from various sources is becoming increasingly crucial to meeting the rising needs of the world's population. Nevertheless, energy storage plays a vital role in meeting the energy demand, notably since affordable yet eco-friendly sources should meet it. Several recommendations were provided to overcome this limitation, with an increasing emphasis on energy sources. However, ecologically sustainable, and effective energy storage systems are the primary focus. Carbonaceous substances produced by pyrolyzing biomass, such as biochar, have recently gained attention as a sustainable material with the potential to be used in electrochemical energy storage technologies. It is an attractive option for electrode materials in supercapacitors, batteries, and hydrogen storage devices due to its abundant availability and distinct physicochemical characteristics, which include, excellent electric conductivity, tuneable surface functional groups, a densely porous structure, a high surface area, porosity, chemical stability, and pore volume. This review addresses the electrochemical performance, production, and characterization of materials based on biochar for energy storage developments. It investigates the choice of feedstock, various preparation routes, various controlling parameters for producing biochar, the biochar activation process, and post-treatment techniques that affect the electrochemical and structural characteristics of biochar for energy storage device fabrication in detail. Additionally, it reveals that recent developments in biochar modification methods like doping, activation, and hybridization have improved the material's capacity for energy storage. Furthermore, an in-depth discussion on the environmental impacts of biochar-based energy storage devices is elaborated, along with the opportunities and challenges presented in this study.